2020
DOI: 10.1101/2020.12.16.423113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long SARS-CoV-2 nucleocapsid sequences in blood monocytes collected soon after hospital admission

Abstract: Many viruses infect circulating mononuclear cells thereby facilitating infection of diverse organs. Blood monocytes (PBMC) are being intensively studied as immunologic and pathologic responders to the new SARS-CoV-2 virus (CoV19) but direct evidence showing CoV19 in monocytes is lacking. Circulating myeloid cells that take up residence in various organs can harbor viral genomes for many years in lymphatic tissues and brain, and act as a source for re-infection and/or post-viral organ pathology. Because nucleoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…One possibility is that ACE2 translocation is an early event during infection, and infected cells quickly migrate to local organs or quickly undergo pyroptosis 14 . A recent preprint study showing that long SARS-CoV-2 nucleocapsid (N) RNA transcripts were identified in PBMCs from 2 of 11 COVID-19 patients as early as 2 to 6 days after hospital admission 40 . Junqueira's study 14 also showed SARS-CoV-2 N proteins were identified in two minor monocyte subsets (intermediate and non-classical) isolated from 12 COVID-19 patients, and ACE2 surface protein levels were significantly increased in monocytes purified from 4 COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that ACE2 translocation is an early event during infection, and infected cells quickly migrate to local organs or quickly undergo pyroptosis 14 . A recent preprint study showing that long SARS-CoV-2 nucleocapsid (N) RNA transcripts were identified in PBMCs from 2 of 11 COVID-19 patients as early as 2 to 6 days after hospital admission 40 . Junqueira's study 14 also showed SARS-CoV-2 N proteins were identified in two minor monocyte subsets (intermediate and non-classical) isolated from 12 COVID-19 patients, and ACE2 surface protein levels were significantly increased in monocytes purified from 4 COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there is still controversy amongst the literature about the susceptibility of human PBMCs to SARS-CoV-2 [50,51]. Although SARS-CoV-2 was detected in immune cells of COVID-19 patients [51][52][53], it remains to be determined whether enhanced activation of the eIF2 pathway in Δ382 SARS-CoV-2 infected patients is directly caused by a loss of ORF8's impact on ER quality control or due to secondary peripheral immune responses to the mutant virus infection, mediated by soluble factors.…”
Section: Discussionmentioning
confidence: 99%
“…Установлена длительная персистенция вируса в ЖКТ, дыхательных путях, нервной системе, моноцитах, макрофагах [32][33][34][35][36][37][38].…”
Section: этиология и патогенез поражений органов пищеварения при пост...unclassified